Cabozantinib in patients with unresectable and progressive metastatic phaeochromocytoma or paraganglioma (the Natalie Trial): a single-arm, phase 2 trial - Jimenez, Camilo; Habra, Mouhammed Amir; Campbell, Matthew T; Tamsen, Gina; Cruz-Goldberg, Damaris; Long, James; Bassett, Roland; Dantzer, Robert; Balderrama-Brondani, Vania; Varghese, Jeena; Lu, Yang (The lancet oncology, 2024)
Metastatic phaeochromocytomas and paragangliomas (MPPGs) are orphan diseases. Up to 50% of MPPGs are associated with germline pathogenic variants of the SDHB gene. These tumours and many non-familial MPPGs exhibit a phenotype that is characterised by abnormal angiogenesis. We aimed to assess the activity and safety of cabozantinib, an antiangiogenic multi-tyrosine kinase inhibitor, in patients with MPPGs. The Natalie Trial is a single-arm, phase 2 clinical trial being conducted at The University of Texas MD Anderson Cancer Center (Houston, TX, USA). Patients aged 18 years or older with histologically confirmed, progressive, and unresectable MPPGs, with an Eastern Cooperative Oncology Group performance status of 0–2, were treated with oral cabozantinib 60 mg/day. The primary endpoint was the investigator-assessed overall response rate per the Response Evaluation Criteria in Solid Tumours version 1.1 criteria. All outcomes were assessed in all evaluable participants who received any amount of study treatment. The trial is registered with ClinicalTrials.gov (NCT02302833) and is active but not recruiting. From March 10, 2015, to May 11, 2021, 17 patients (13 male participants and four female participants) were enrolled. The median follow-up was 25 months (IQR 18–49). The overall response rate was 25·0% (95% CI 7·3–52·4; four of 16 patients). Seven grade 3 adverse events were reported in six patients, including single cases of hand-and-foot syndrome, hypertension, rectal fistula, QT prolongation, and asymptomatic hypomagnesaemia, and two cases of asymptomatic elevations of amylase and lipase. There were no grade 4 adverse events and no patient died on-study. Cabozantinib shows promising activity in patients with MPPGs. Team NAT Foundation, Margaret Cazalot, and Clarence P Cazalot.